(untitled) (INNOVATIVE ECONOMY, 2020)
Dermanska L.V. CUSTOMS CONTROL OPTIMIZATION FOR PROVIDING EFFICIENCY OF FOREIGN ECONOMIC ACTIVITY Purpose. The aim of the article is to investigation of problem areas of customs control and development of ways to optimize its procedures for ensuring the effectiveness of foreign economic activity. Methodology of research. To study the problem, general scientific and special methods were used: dialectical, deductive, inductive, abstraction and concretization, comparative and statistical analysis, graphical method. The following methods of research are used in the article: dialectical method of knowledge – in considering planning and substantiation of the concept of customs control; abstract and logical – in the theoretical generalization of the essence and methods of management mechanisms of customs control. Findings. The importance of optimization of customs procedures in the direction of integration into the European trading space is determined, the relationship of customs procedures on the effectiveness of customs control is investigated and the problem directions of their implementation are highlighted. The state measures on simplification and harmonization of customs rules in Ukraine are analyzed and priority directions of the customs policy in this direction from 2018 are outlined. The principles of effectiveness of customs reform are defined for ensuring development of foreign economic relations and socio and economic development of the state. According to the results of the conducted research, we note that customs control should ensure the achievement of the aim of customs policy - the positive image of Ukraine, its influence on the development of foreign economic relations and socio and economic development of the state as a whole. Originality. System research of problem areas of optimization of customs procedures for ensuring the effectiveness of customs control and development of foreign economic activity is carried out. Practical value. The obtained results of the research will contribute to a significant improvement of the state of customs control, increase of efficiency of control and checking activity of customs units, strengthening of their role in counteraction to shadow transactions in the field of foreign economic activity. Key words: customs procedures; customs control; European integration; foreign trade; efficiency; optimization.